Kloning Manusia dan Masalah Sosial-Etik - Aman * (Pendidikan Sosiologi FIS UNY, 2007)
In the context of Sociological, human cloning has been taken into consideration of endangering and threatening the social order which has been developed by man since their existence on earth. Cloning is also bringing negative upshot not only to social order but also to the social interaction which has been accepted as the basis of the harmony and peace between individual. The biological technology utilization was once only laid a hand on scientific knowledge ever since it was resulted on or after scientific exploration process. Yet directly or indirectly, cloning might originate the devastation of the basic principle of religion with its universal ethics. Cloning not only lies in the scientific land but further, it has made a long jump over the discipline of science such as ethic, Sociology, Economy, gender and religion. Keywords: human cloning, social problems, ethic, religion